A Simplified Post Equalizer for Mitigating the Nonlinear Distortion in SiPM Based OFDM-VLC System - Long Zhang (IEEE, 2022)
The silicon photomultiplier (SiPM) based orthogonal frequency division multiplexing (OFDM) system is a promising solution to realize both the longer distance and higher data rate in visible light communication (VLC). However, it suffers from nonlinear distortions induced by SiPM. The Volterra nonlinear equalization (VNLE) is commonly used at the receiver to compensate for the nonlinear distortions, but it has a huge implementation complexity. As an alternative, the memory polynomial based equalization (MPE) offers significantly reduced complexity but at the cost of degrading BER performance. In this paper, we propose and demonstrate a promising simplified VNLE equalizer for SiPM based OFDM-VLC systems according to SiPM's characteristics. Results show that the proposed equalizer outperforms the MPE in terms of BER and significantly reduces the computational complexity of the conventional VNLE. With the proposed equalization scheme, a data rate of 1.35Gbps has been achieved. To the best of the author's knowledge, this is the highest data rate achieved using SiPM in VLC with optical OFDM.